Engraving of Isle de France-P6280124 - Auteur inconnu (Wikimedia Commons, 1850)
Notice iconographique issue de Wikimedia Commons. Titre: Engraving of Isle de France-P6280124. Engraving of Isle de France showing "Trou Fanfaron" at Port Napoleonéon (now Port Louis)
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons